Anterior Clinoid Mucocele—Clinical Presentation, Investigations, and Management by Endoscopic Excision: Review of Literature - Kuruvath, Sarin; Ahmed, Shahzada; Johnson, Alan; Shad, Amjad (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Mucoceles in the anterior clinoid location are exceptionally rare. They present with visual failure and are often misdiagnosed as unilateral optic neuritis. Early recognition with imaging studies and prompt surgical excision is the treatment of choice. Endoscopic surgery achieves this with the least surgical trauma and hospitalization. We report two cases of anterior clinoid mucocele that were treated successfully by endoscopic surgery and also review its management.
Keywords: anterior clinoid process; mucocele; optic neuropathy; endoscopic sinus surgery